Plunder : a memoir of family property and Nazi treasure - Kaiser, Menachem, 1985- (Houghton Mifflin Harcourt, 2021)
"From a gifted young writer, the story of his quest to reclaim his family's apartment building in Poland-and of the astonishing entanglement with Nazi treasure hunters that follows"--